2014
DOI: 10.1002/sca.21185
|View full text |Cite
|
Sign up to set email alerts
|

The effects of UV irradiation on collagen D-band revealed by atomic force microscopy

Abstract: The objective of this paper was to investigate the influence of UV irradiation on collagen D-band periodicity by using the AFM imaging and nanoindentation methods. It is well known than UV irradiation is one of the main factors inducing destabilization of collagen molecules. Due to the human's skin chronic exposure to sun light, the research concerning the influence of UV radiation on collagen is of great interest. The impact of UV irradiation on collagen can be studied in nanoscale using Atomic Force Microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 42 publications
(79 reference statements)
3
58
0
Order By: Relevance
“…One of the factors that can easily cause LEC damage is UV. Numerous studies have shown (1416) that UV radiation is closely related to the occurrence of cataract. LEC apoptosis is the initiation of cataract, in which p53 has a strong ability to regulate cell growth (17).…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that can easily cause LEC damage is UV. Numerous studies have shown (1416) that UV radiation is closely related to the occurrence of cataract. LEC apoptosis is the initiation of cataract, in which p53 has a strong ability to regulate cell growth (17).…”
Section: Discussionmentioning
confidence: 99%
“…As it has been previously reported for spherical indenters, if the indenter's radius is at least ten times smaller from each horizontal dimension of the sample, then the sample can be considered as an elastic half space [13]. In addition, the maximum indentation depth should not exceed the 5%-10% of the sample's thickness in order to avoid measuring the sample's substrate properties (Buckle's rule) [12].…”
Section: The Hertz Modelmentioning
confidence: 99%
“…AFM nanoindentation experiments on biological samples 2.1.1. Loading and unloading curves In a typical AFM nanoindentation experiment the AFM tip indents the sample of interest and a loaddisplacement curve is recorded [9,12]. The same procedure is also performed on a hard reference sample [9,12].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic force microscopy (AFM) based nanoindentation has been well established as a powerful technique for the investigation of the mechanics at the nanoscale level916171819. To have a better understanding of the effect of abnormal calcium homeostasis on soft tissues’ mechanics, we attempted to employ AFM-based nanoindentation to study the mechanical behavior of type II collagen fibril extracted from AC.…”
mentioning
confidence: 99%